2009
DOI: 10.1091/mbc.e09-01-0094
|View full text |Cite
|
Sign up to set email alerts
|

LULL1 Retargets TorsinA to the Nuclear Envelope Revealing an Activity That Is Impaired by theDYT1Dystonia Mutation

Abstract: TorsinA (TorA) is an AAA؉ ATPase in the endoplasmic reticulum (ER) lumen that is mutated in early onset DYT1 dystonia. TorA is an essential protein in mice and is thought to function in the nuclear envelope (NE) despite localizing throughout the ER. Here, we report that transient interaction of TorA with the ER membrane protein LULL1 targets TorA to the NE. FRAP and Blue Native PAGE indicate that TorA is a stable, slowly diffusing oligomer in either the absence or presence of LULL1. Increasing LULL1 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
162
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(178 citation statements)
references
References 49 publications
12
162
0
1
Order By: Relevance
“…On the other hand, overexpression of LAP1 and LULL1 recruits torsinA to the nuclear envelope [11,28]. A recent study reported that ATPase activity of torsinA is induced in the presence of LAP1 or LULL1 and that LAP1 and LULL1 are regulatory cofactors of torsinA [12].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, overexpression of LAP1 and LULL1 recruits torsinA to the nuclear envelope [11,28]. A recent study reported that ATPase activity of torsinA is induced in the presence of LAP1 or LULL1 and that LAP1 and LULL1 are regulatory cofactors of torsinA [12].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the impaired interaction between the ⌬E-torsinA and the lumenal domain of LAP1 (Fig. 5), probably as well as other NE proteins such as SUNs and nesprins (24,26), would explain the dystonia-associated disruption of the neuronal nuclear envelope (44,46) arising from the inability of LAP1 to maintain nuclear structure during neuronal maturation. LULL1 shares remarkable similarities with LAP1, suggesting that the N-terminal cytoplasmic domain of LULL1 may interact with some unknown molecules in the cytoplasm, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that torsinA may act on substrate(s) both in the nuclear envelope (NE) and in the ER (21,22). Two putative substrates have been identified: laminaassociated polypeptide 1 (LAP1) in the NE and lumenal domain like LAP1 (LULL1) in the ER (23)(24)(25). Consistent with the NE localization, torsinA has been reported to associate with outer nuclear membrane proteins, including SUNs (24) and nesprins (26) and some cytoskeletal components such as vimentin and actin (27), implicating its roles in NE structure regulation, cell adhesion, and neurite extension.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…TorsinA is partitioned between the ER and the contiguous perinuclear space of the nuclear envelope, and its localization is controlled in part by its association with LAP1 and LULL1, type II transmembrane proteins residing in the nuclear envelope and ER, respectively (12)(13)(14). Another unusual property of Torsins is that they lack significant basal ATPase activity in isolation and are tightly regulated by LAP1 and LULL1, which integrate into the Torsin ring via AAA-like domains to trigger ATP hydrolysis through an active site complementation mechanism (15)(16)(17).…”
mentioning
confidence: 99%